Data Hiding Based DNA Issues: A Review (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
Security of Information are a key concern, particularly with the extension growth of internet usage. This growth comes the incidents of unauthorized access which are countered by the use of varied secure communication techniques, namely; cryptography and data hiding. More recent trends are concerned with DNA used for cryptography and data hiding as a carrier exploiting its bio-molecular properties. This paper provides a review about published DNA based data hiding techniques using the DNA as a safeguard to critical data that transmitted on an insecure channel, to find out the strength and weaknesses points of them. This will help the future research in designing of more efficient and secure data hiding techniques-based DNA.